Modern Control Approaches for a Wind Energy Conversion System based on a Permanent Magnet Synchronous Generator (PMSG) Fed by a Matrix Converter - Gaurav Bharadwaj; Satyanarayan Joshi; Ravindra Singh Chauhan; Virendra Kumar Sharma; Jitendra Kumar Deegwal (International Journal of Engineering and Management Research, 2022)
This “paper proposes a super-twisting adaptive Control Approaches for a Wind Energy Conversion System Based on a Permanent Magnet Synchronous Generator (PMSG) Fed by a matrix sliding mode for tracking the maximum power point of wind energy conversion systems using permanent magnet synchronous generators (PMSGs). As the adaptive control algorithm employed retains the robustness properties of classical wind energy conversion system control methods when perturbations and parameter uncertainties are present, it can be considered an effective solution; at the same time, it reduces chattering by adjusting gain and generating second-order adaptive control methods. The Egyptian power system (EPS), a three-zone interconnected microgrid (MG), and a single machine linked to the grid are only a few examples of the power systems for which this article introduces the concept of direct adaptive control (SMIB).The goal of our work is to maximize the captured power by solving a multi-input multi-output tracking control problem. In the presence of variations in stator resistance, stator inductance, and magnetic flux linkage, simulation results are presented using real wind speed data and discussed for the proposed controller and four other sliding mode control solutions for the same problem. The proposed controller achieves the best trade-off between tracking performance and chattering reduction among the five considered solutions: compared to a standard sliding mode control algorithm, it reduces chattering by two to five orders of magnitude, and steadystate errors on PMSG rotor velocity by one order of magnitude”. The purpose of this article is to examine wind turbine control system techniques and controller trends related to permanent magnet synchronous generators. The article presents an overview of the most popular control strategies for PMSG wind power conversion systems. There are several kinds of nonlinear sliding modes, such as direct power, backstepping, and predictive currents. To determine the performance of each control under variable wind conditions, a description of each control is presented, followed by a simulation performed in MATLAB /Simulink. This simulation evaluates the performance of each control in terms of reference tracking, response times, stability, and signal quality. Finally, this work was concluded with a comparison of the four controls to gain a better understanding of their effects. “Moreover, it reduces the above-mentioned steady-state error by four orders of magnitude compared to a previously-proposed linear quadratic regulator based integral sliding mode control law. A dynamic model is simulated under both variable step and random wind speeds using the DEV-C++ software, and the results are plotted using MATLAB. The obtained results demonstrate the robustness of the proposed controller in spite of the presence of different uncertainties when compared to the classical direct torque control technique.